Robust vehicle localization based on multi-level sensor fusion and online parameter estimation - Bevermeier, Maik; Peschke, Sven; Haeb-Umbach, Reinhold (6th Workshop on Positioning Navigation and Communication (WPNC 2009))
In this paper we present a novel vehicle tracking algorithm, which is based on multi-level sensor fusion of GPS (global positioning system) with Inertial Measurement Unit sensor data. It is shown that the robustness of the system to temporary dropouts of the GPS signal, which may occur due to limited visibility of satellites in narrow street canyons or tunnels, is greatly improved by sensor fusion. We further demonstrate how the observation and state noise covariances of the employed Kalman filters can be estimated alongside the filtering by an application of the Expectation-Maximization algorithm. The proposed time-variant multi-level Kalman filter is shown to outperform an Interacting Multiple Model approach while at the same time being computationally less demanding.
Keywords: covariance matrices; expectation-maximisation algorithm; expectation-maximization algorithm; global positioning system; Global Positioning System; GPS; inertial measurement unit; interacting multiple model approach; Kalman filters; multilevel sensor fusion; narrow street canyons; narrow tunnels; online parameter estimation; parameter estimation; road vehicles; robust vehicle localization; sensor fusion; state noise covariances; time-variant multilevel Kalman filter; vehicle tracking algorithm